Peran Moderasi Islamic Marketing Ethic terhadap Keputusan menjadi Nasabah Bank Syariah - Zaha, Ali Purnama; Jumriani, Jumriani (Islamic Banking and Finance, 2023)
In this study, it discusses the moderating role of Islamic marketing ethics on the influence of the decision to become a customer of an Islamic bank (studies at BSI KC Bone) and is analyzed using a quantitative research type. In this study three research question were proposed, namely: (1) the effect of attitudes and subjective norm on the decision to become a customer of an Islamic bank, (2) the effect of Islamic marketing ethics on the decision to become a customer of an Islamic bank, and (3) Islamic marketing ethics moderates the influence of attitudes and subjective norm of the to become a customer of Islamic banks. To answer these three research questions, statistical data were collected through questionnaires which were distributed to customers of the Indonesian Islamic bank (BSI) KC Bone as many as 100 using simple linear regression analysis through the smart PLS application.